2018
DOI: 10.1016/j.tiv.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into E-cigarette cytotoxicity in-vitro using a novel 3D differentiated co-culture model of human airways

Abstract: Currently there is a lack of consensus on the possible adverse health effects of E-cigarettes (ECs). Important factors including cell model employed and exposure method determine the physiological relevance of EC studies. The present study aimed to evaluate EC cytotoxicity using a physiologically relevant in-vitro multicellular model of human airways. Human bronchial epithelial cells (CALU-3) and pulmonary fibroblasts (MRC-5) were co-cultured at air-liquid-interface for 11-14 days post which they were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…However, increased levels of the proinflammatory cytokine, TNF-α, were observed following 6, 24 and 48 h of LPS exposure, and increased levels of IL-1β, IL-6 and IL-8 were observed across all time intervals from 6 to 48 h, which indicated that these cytokines may be important factors for maintaining persistent inflammation. Some co-culture models of chronic inflammatory have been studied for more than 7 days (19,28); in the current study, EpCs and MPs viability following LPS treatment was monitored for 7 days; however, the A549 (EpCs) cells began to die after 72 h (the OD value was quite low), whereas THP-1 cells (MPs) grew well from 0 to 7 days (data not shown). In a previous study, the inflammatory status of airway epithelial cells and MPs was determined at 24 and 48 h (29), thus in the present study, the inflammatory effects were observed until up to 48 h of co-culture.…”
Section: Discussionmentioning
confidence: 78%
“…However, increased levels of the proinflammatory cytokine, TNF-α, were observed following 6, 24 and 48 h of LPS exposure, and increased levels of IL-1β, IL-6 and IL-8 were observed across all time intervals from 6 to 48 h, which indicated that these cytokines may be important factors for maintaining persistent inflammation. Some co-culture models of chronic inflammatory have been studied for more than 7 days (19,28); in the current study, EpCs and MPs viability following LPS treatment was monitored for 7 days; however, the A549 (EpCs) cells began to die after 72 h (the OD value was quite low), whereas THP-1 cells (MPs) grew well from 0 to 7 days (data not shown). In a previous study, the inflammatory status of airway epithelial cells and MPs was determined at 24 and 48 h (29), thus in the present study, the inflammatory effects were observed until up to 48 h of co-culture.…”
Section: Discussionmentioning
confidence: 78%
“…Numerous studies have evaluated the potential toxicity of ECs in vitro [1014]; however, a large number of in vitro studies examined the effects of the EL that were applied directly on cell cultures but not the effects of exposure to the vapor/aerosol [1522]. Although such studies may provide insights into the potential toxicity of the EL, they do not reflect the real exposure to EC; in reality, the human respiratory system is exposed to the EC aerosols and not to the EL.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is a lack of consensus on the possible harmful effects of e-cigarette vapor on a 3D differentiated co-culture model of human airways. The study, conducted on a multicellular model of human cells comprising human bronchial epithelial cells (CALU-3) and pulmonary fibroblasts (MRC-5), indicate that exposure to e-liquid ingredients including PG:VG, 16 mg/mL nicotine and proprietary flavors significantly impact cell viability, proinflammatory mediator production and oxidative stress [118]. In turn, a study on EpiAirway tissue, a human airway culture derived from primary human tracheal/bronchial epithelial cells, demonstrated similar cell viability to untreated controls following exposure to commercially available e-cigarette aerosols, with and without menthol flavoring, containing 4.5% and 3% nicotine by volume [119].…”
Section: In Vitro Studies On E-liquid Exposure To Cellsmentioning
confidence: 99%